Meningkatkan Disiplin Waktu AUD Melalui Teknik Modifikasi Perilaku Token Economic Dengan Pemberian Kupon - Niken Ayu Nila Ariani; Ari Purnomo Endah Aflahani (JURNAL LENTERA ANAK, 2021)
This study aims to improve disciplinary behavior in early childhood through  the application of the "Token Economic" behavior modification technique.by giving coupons. The problem in this research is that early childhood has a lot of activity so they don't have time to play and lack of rest. Thus, children become lazy and result in children being undisciplined with time. The reason for choosing the topic in this research is that there are children who lack discipline to wards time. So there needs to be an effort to improve the discipline of children's time. The method used in this research is descriptive qualitative with a case study approach. The hypothesis proposed in this study is "There is an increase in discipline in children". Data collection methods used are interviews, observation, and documentation because they can describe the situation accurately. The results showed that from meeting 1 to meeting 7 the child's behavioral targets had been achieved as expected. The child is able to perform the task as well possible according to the agreed contract. Children fell happy to do this activity with out feeling forced.